Effects of Leaf Extracts of Murraya koenigii (Rutaceae) on Coptotermes curvignathus (Isoptera: Rhinotermitidae). - Safian, Asfezan; Sajap, Ahmad Said; Md.Sukari, Mohd. Aspollah; Abood , Faizah; Abu Bakar, Noor Haslizawati; Mohamad Kasim, Mohamad Roslan (Universidade Estadual de Feira de Santana, 2011)
Hexane, chloroform and methanol extracts from leaves of Murraya koenigii (Rutaceae) were tested for their termiticidal effects on subterranean termites, Coptotermes curvignathus Holmgren (Isoptera: Rhinotermitidae). The results show that the termite workers responded differently to filter papers that had been treated with varying concentrations of the leaf extracts. The hexane extracts generally had the highest repellent activity on the termites and all extracts significantly affected the mortality and feeding rates of the termites. The mortality rates ranged from 27 to 31% in hexane, 7 to 23% in chloroform and 52 to 60% in methanol extracts. The mortality rates from the controls in all treatments were less than 10%. The termites consumed less than 10% of the treated filter papers as compared to more than 35% of the untreated filter papers. The experiment thus shows that leaf extracts of M. koenigii contained biologically active compounds that were repellent and affected feeding and survival of C. curvignathus.